2014
DOI: 10.1016/j.pain.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Altered experimental pain perception after cerebellar infarction

Abstract: Animal studies have suggested that the cerebellum, in addition to its motor functions, also has a role in pain processing and modulation, possibly because of its extensive connections with the prefrontal cortex and with brainstem regions involved in descending pain control. Consistently, human imaging studies have shown cerebellar activation in response to painful stimulation. However, it is presently not clear whether cerebellar lesions affect pain perception in humans. In the present study, we used experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 53 publications
6
99
0
Order By: Relevance
“…The present meta-analysis identified abnormalities in cerebellar lobule VIII, which is predominantly associated with sensorimotor function, and in lobules VIIb and Crus II, which are associated with higher-order (e.g., executive, emotional, and cognitive) processing [72][73][74][75][76][77][78], This suggests that the cerebellum has a previously underestimated role in patients with fibromyalgia, which might be of further interest and should be given more emphasis in future investigations.…”
Section: The Cerebellummentioning
confidence: 51%
See 1 more Smart Citation
“…The present meta-analysis identified abnormalities in cerebellar lobule VIII, which is predominantly associated with sensorimotor function, and in lobules VIIb and Crus II, which are associated with higher-order (e.g., executive, emotional, and cognitive) processing [72][73][74][75][76][77][78], This suggests that the cerebellum has a previously underestimated role in patients with fibromyalgia, which might be of further interest and should be given more emphasis in future investigations.…”
Section: The Cerebellummentioning
confidence: 51%
“…This involves it in many cerebro-cerebellar circuits. Research implicates these circuits not only in sensorimotor processing but also in cognitive and affective functions, and more recently in pain perception and modulation [72][73][74][75][76][77][78]. Recent brain structural covariance network analysis of patients with fibromyalgia compared with healthy controls showed denser connections in the cerebellum and less-dense connections in the frontal lobe [39].…”
Section: The Cerebellummentioning
confidence: 99%
“…However, few patient studies have been performed. Three studies have shown impaired offset analgesia in patients: one in diabetic polyneuropathy [77], one in cerebellar infarction [82], and one in painful neuropathic pain [69]. So far, no studies have been performed in patients with chronic joint pain.…”
Section: Offset Analgesiamentioning
confidence: 99%
“…For allanalyses, theselected pthresholdwasselected using theFalse Discovery Rate with positive dependence assumption, FDRpN<0.05 andminimum clusters extent Ke> 500 mm 3 .Weused Chris Rorden's MRIcron software (http://www.nitrc.org/projects/mricron)to visualize and save images, overlayingtheGingerAle maps ontoaTalairachbrain template (created by [40]). …”
Section: Meta-analysismentioning
confidence: 99%
“…The cerebellum has been considered to be involved in pain processing: for instance, in rats, pain stimulation evokes changes in neural activity inthe posterior cerebellar vermis [2],andin humans, cerebellar lesion alteredpain perception [3].Asshowninalargefunctional magnetic resonance imaging-positron emission tomography (fMRI-PET) meta-analysis [4], the cerebellum is activated during painrelatedstimulation in conjunction with the areas typically associated with pain: the bilateral insula (with a right dominance),anterior cingulatecortex(ACC),bilateralprimary motor/sensory cortex (MI/SI), secondary somatosensory cortex (SII), posterior parietal cortex, andprefrontal cortex. Specifically, the nociceptive-related activation was observed in the deep cerebellar nuclei andanterior vermis IV-V, bilaterally in hemispheric lobules VI, VIIb, crus 1, and crus 2.…”
Section: Introductionmentioning
confidence: 99%